2015
DOI: 10.1364/oe.23.014666
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Colliding Pulse Mode-locked laser diode (OCCP-MLLD) using multimode interference reflectors

Abstract: We report the achievement of colliding pulse mode-locked (CPM) regimes on a novel on-chip mode locked laser diode (OCCP-MLLD). The advantage of the resonator structure that we present is that the end-mirrors are defined through multimode interference reflectors (MIRs), which provide precise control of the cavity length avoiding the need for cleaved facets. This simplifies positioning the saturable absorber at the center of the resonator to achieve the colliding pulse mode-locked regime and double the repetitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…From these measurements, we have identified that autocorrelation traces are key to optimize the interleaver performance, which require fine tuning of the repetition rate to match the designed delays. The quality of the electrical signal that is generated from mCPML structures in the passive mode locking regime has been already presented, comparing the electrical linewidth of devices with repetition rate frequencies falling within the range of our electrical spectrum analyzer (up to 40 GHz) with devices requiring an external mixer head [20]. Previous results show that the electrical linewidth from the core MLL is within the MHz range, as is usual for passive mode locked semiconductor lasers operating at the fundamental frequency.…”
mentioning
confidence: 63%
“…From these measurements, we have identified that autocorrelation traces are key to optimize the interleaver performance, which require fine tuning of the repetition rate to match the designed delays. The quality of the electrical signal that is generated from mCPML structures in the passive mode locking regime has been already presented, comparing the electrical linewidth of devices with repetition rate frequencies falling within the range of our electrical spectrum analyzer (up to 40 GHz) with devices requiring an external mixer head [20]. Previous results show that the electrical linewidth from the core MLL is within the MHz range, as is usual for passive mode locked semiconductor lasers operating at the fundamental frequency.…”
mentioning
confidence: 63%
“…1(a) is composed of a saturable absorbor (SA), semiconductor optical amplifiers (SOA), electro-optic phase modulators (EOPM), multimode interference reflectors (MIR) and straight/bent passive waveguides in a symmetric geometry with respect to the SA. This symmetry configuration assures operation in colliding-pulse mode locking regime [29], and the total cavity length defined by MIRs is 3.78 mm corresponding to a repetition rate of about 21.5 GHz. This 30-μm SA is surround by two 400-μm SOAs with two 1200-μm-long EOPMs on both sides.…”
Section: Introductionmentioning
confidence: 97%
“…For this reason, harmonic mode-locked (HML) structures have been investigated to overcome this limit and increase the RR without reducing the cavity length, by generating different pulses per round trip, effectively multiplying the fundamental RR of the cavity [8]. Harmonic mode-locking has been demonstrated using a variety of techniques, from colliding pulse mode-locked lasers (CPMLLs) [9], [10], coupled-cavity mode-locking [11], methods based on the wavelength selectivity of distributed Bragg reflector (DBR) grating [12] or compound cavity laser [13]. In the CPMLL structure, one saturable absorber is located at the laser resonator center, which results in two optical-counter-propagating pulses in the cavity that meet at the SA.…”
mentioning
confidence: 99%